Ira Aldridge : the early years, 1807-1833. - Lindfors, Bernth (Rochester studies in African history and the diaspora, 2014)
Ira Aldridge: The Early Years, 1807-1833 chronicles the rise of one of the modern world's first black classical actors, as he ascended from an impoverished childhood in New York City to a career as a celebrated thespian on the British stage. After a successful debut in London in 1825, Aldridge began touring the British provinces, billing himself grandiloquently as the ""African Roscius, "" and attracting crowds with his powerful presence and style. He received accolades not only as a tragedian in classic roles such as Othello and Oroonoko but also as a comic actor in popular farces and mu.